MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATA KULIAH PENGETAHUAN LINGKUNGAN HIDUP MELALUI PENDEKATAN SCIENTIFIC MAHASISWA - Muh Rapi (Jurnal Biotek, 2016)
This study aims to determine the increased activity of learning and learning outcomes by applying a scientific approach to the subject of environmental science students of Biology Education Studies Program class of 2013. The research is a classroom action research design model Sanford and Kemmis shaped cycle consists of four phases , namely: 1) planning, 2) acting, 3) observing, and 4) reflecting. Data were analyzed descriptively qualitative and quantitative descriptive. The research found the application of a scientific approach to learning courses environmental knowledge can improve students' learning activities. Scores acquisition of learning activities of students on the learning aspects observed in the first cycle with the average percentage of 72.36% and the second cycle increased to an average 84.76%. This means an increase of 12.40%. Similarly, the student results with the application of scientific approach tends to increase from the first cycle to the second cycle. It can be seen from the average score obtained by increasing that average 77.56 students in the first cycle to average 83.78 in the second cycle. Thus an increase in the score results learned from the first cycle to the second cycle of 6.22.